2019
DOI: 10.1111/bph.14594
|View full text |Cite|
|
Sign up to set email alerts
|

Potent effects of dioscin against hepatocellular carcinoma through regulating TP53‐induced glycolysis and apoptosis regulator (TIGAR)‐mediated apoptosis, autophagy, and DNA damage

Abstract: Background and purpose: Dioscin shows potent effects against cancers. We aimed to elucidate its pharmacological effects and mechanisms of action on hepatocellular carcinoma (HCC) in vivo and in vitro.Experimental approach: Effects of dioscin were investigated in SMMC7721 and HepG2 cells, diethylnitrosamine-induced primary liver cancer in rats, and cell xenografts in nude mice. Isobaric tags for relative and absolution quantitation (iTRAQ)based proteomics was used to find dioscin's targets and investigate its m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 52 publications
3
27
0
Order By: Relevance
“…A recent study has demonstrated that dioscin, a natural steroid saponin, decreased the expression levels of TIGAR and induced cell apoptosis of hepatocellular carcinoma in vitro and in animal model through the involvement of upregulating Bax, caspase-3, 9, PARP, and downregulating Bcl-2 expression. [16] Similar results have been obtained with decrease of TIGAR protein in MCF-7 cell lines. [45] In our study, the downregulation of intact 116 kDa PARP content could reflect a decrease in the capability to repair DNA damage in TIGAR depleted A549-Dox cells in comparison to A549-Dox line.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A recent study has demonstrated that dioscin, a natural steroid saponin, decreased the expression levels of TIGAR and induced cell apoptosis of hepatocellular carcinoma in vitro and in animal model through the involvement of upregulating Bax, caspase-3, 9, PARP, and downregulating Bcl-2 expression. [16] Similar results have been obtained with decrease of TIGAR protein in MCF-7 cell lines. [45] In our study, the downregulation of intact 116 kDa PARP content could reflect a decrease in the capability to repair DNA damage in TIGAR depleted A549-Dox cells in comparison to A549-Dox line.…”
Section: Discussionsupporting
confidence: 79%
“…[11] Studies have shown that metastasis, the major cause of the deaths at cancer, is directly related to the mesenchymal properties of tumor cells. [12,13] Although the biology of TIGAR has been studied in apoptosis and autophagy in detail, [8,[14][15][16] the role of TIGAR in EMT of lung cancer cells is scarcely reported, and the participation of TIGAR in Dox-resistance of lung cancer cell is yet to be elucidated. Therefore, this study aimed to reveal the role of TIGAR protein in the development of doxorubicin resistance of A549 lung carcinoma cells (A549/ DOX).…”
Section: Introductionmentioning
confidence: 99%
“…November 2020 | Volume 11 | Article 563750 activated in the liver and can regulate the transcription of downstream genes, including Bcl-2 and Bax (Mao et al, 2019b). Bcl-2, an antiapoptotic factor, can inhibit apoptosis and promote cell growth by binding to the proapoptotic factor Bax (Willis et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis, oxidative stress, and inflammatory responses were evident after treatment with CP ( Rehman et al, 2014 ), which was also confirmed by our results of network pharmacology. p53 can be activated in the liver and can regulate the transcription of downstream genes, including Bcl-2 and Bax ( Mao et al, 2019b ). Bcl-2, an antiapoptotic factor, can inhibit apoptosis and promote cell growth by binding to the proapoptotic factor Bax ( Willis et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional chinese medicines have been used to treat cancer for thousands of years, using a large collection of biologically active products (18)(19)(20)(21). natural compounds from medicinal plants, including dioscin and berberine, have potent effects against various types of cancer (22)(23)(24)(25)(26)(27)(28); it is reported that berberine inhibited human cervical carcinoma Hela cells and dioscin induced dna damage and activated mitochondrial signal pathway in human a549, nci-H446 and nci-H460 cancer cell lines (29,30). additionally, some natural products, including genistein and daidzein, have been reported to inhibit migration, invasion and proliferation of oVca cells (31).…”
Section: Introductionmentioning
confidence: 99%